Prevalence of fistula-in-ano in patients attending tertiary care institute of Gujarat: a cross-sectional study - Sukhlecha, Akhilesh G. (International Surgery Journal, 2019)
Background: Present research was done to study the evidence, etiology signs, symptoms, pathogenesis and management and follow up of the patient for a period of 6 months after surgery. Methods: This was a clinical study of fistula in ano done at medical institute for the period of 1 year. 50 cases, clinically diagnosed, fistula in ano were selected randomly utilizing the closed envelope method and studied. Clinical examination including per rectal and proctoscopic was done in required patients. Patients were treated with fistulectomy or fistulotomy for fistulae. Patients were followed up for a period of 3 months to 1 year. Results: In this present series, 44% of patients were in the age group of 31-40 years. 70% of patients were, discharging wound was the presenting the complaint. 20% of patients with pain and swelling around the anal region. In the study of 50 cases were randomly selected patients of fistula in ano, 84% of them had only one external opening, while 10% had 2 external opening and another 6% had more than 2 openings, hence fistula in ano with a single external opening is commonest in occurrence. Conclusions: On the basis of observations, we can conclude that early diagnosis and appropriate management is the key to success. It not only reduces the complications but also improve the quality of life among these patients.